Refleksi Kedaulatan Negara dalam Penegakan Hukum Sumber Daya Alam Hayati di Zona Ekonomi Eksklusif - Andriani Wahyuningtyas Novitasari (Jurnal Konstitusi, 2020)
The international law regime on EEZ has been developed by the international community through the United Nations Conference on and state practices. This regime is intended to protect the interests of coastal states from the danger of being depleted of biological natural resources by fishing activities based on the free sea regime. In addition, the EEZ is also intended to protect the interests of the coastal state in the field of marine environment conservation as well as marine scientific research in order to support the use of natural resources in the zone. UNCLOS gives sovereign rights to Indonesia as a coastal state to explore and exploit natural resources in the EEZ as well as jurisdictions relating to the exercise of these sovereign rights. For that reason needs integrated law enforcement an effort to conserve living natural resources in ZEE Indonesia. By using the normative legal writing method, this study describes how the concept of law enforcement of living natural resources in Indonesia's EEZ based on various laws and regulations.